2019
DOI: 10.3390/genes10070493
|View full text |Cite
|
Sign up to set email alerts
|

Super-Resolution Microscopy of Chromatin

Abstract: Since the advent of super-resolution microscopy, countless approaches and studies have been published contributing significantly to our understanding of cellular processes. With the aid of chromatin-specific fluorescence labeling techniques, we are gaining increasing insight into gene regulation and chromatin organization. Combined with super-resolution imaging and data analysis, these labeling techniques enable direct assessment not only of chromatin interactions but also of the function of specific chromatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 93 publications
0
15
0
Order By: Relevance
“…What matters is not always the highest resolution, but the right resolution needed to solve a given biological problem. Other parameters are of equal importance, such as structure integrity of the sample, the choice of fluorophores, optimally suited for the labeling of chosen targets with little fluorophore bleaching, optimal signal, and noise levels recorded by detectors with high quantum efficiency, software for image analysis and 3D reconstructions …”
Section: Support Of the Anc‐inc Model With Super‐resolved Fluorescencmentioning
confidence: 99%
“…What matters is not always the highest resolution, but the right resolution needed to solve a given biological problem. Other parameters are of equal importance, such as structure integrity of the sample, the choice of fluorophores, optimally suited for the labeling of chosen targets with little fluorophore bleaching, optimal signal, and noise levels recorded by detectors with high quantum efficiency, software for image analysis and 3D reconstructions …”
Section: Support Of the Anc‐inc Model With Super‐resolved Fluorescencmentioning
confidence: 99%
“…The technical ability to visualize the spatial relationships of multiple proteins in tissues at super‐resolution represents a major capability in the field of microscopy. Applications for studying biological structure with super‐resolution microscopy have grown considerably in the last few years (Birk, 2019; Fang et al., 2018; Garcia et al., 2017; Mockl et al., 2014; Schermelleh et al., 2019; Sieben et al., 2018; Sreedharan et al., 2017; Stracy & Kapanidis, 2017; Xu & Liu, 2019) and new advances in the field are predicted to improve our understanding as the potential of the technology is further realized. In the past, studies of microglia in brain tissue were typically conducted using immunocytochemistry in combination with brightfield, epifluorescence widefield, or confocal microscopy (Sarmiento, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, when assessing chromatin conformation within TADs, subTADs, and particular loop domains, one should consider methods of super-resolution fluorescent (SRM) or electron microscopy. In the last decade, stochastic optical reconstruction microscopy (STORM), photoactivated localization microscopy (PALM), structured illumination microscopy (SIM), focused ion beam scanning electron microscopy (FIB-SEM) were applied intensively in the exploration of chromatin domains within individual cells ( Lakadamyali and Cosma, 2015 ; Birk, 2019 ; Szydlowski et al, 2019 ; Shim, 2021 ; Xie and Liu, 2021 ). Highlights and practical guidance for the application of these microscopy tools is beyond the scope of the present review and can be found elsewhere ( Lambert and Waters, 2017 ; Schermelleh et al, 2019 ).…”
Section: Fish As a An Efficient Approach For Chromatin Domain Visualizationmentioning
confidence: 99%